Pengaruh Takaran Dan Cara Pemberian Pupuk Kandang Burung Puyuh Terhadap Pertumbuhan dan Hasil Cabai Rawit - Paunizar Hernadi; Gusti Rusmayadi; Joko Purnomo (Universitas Lambung Mangkurat, 2019)
Cayenne pepper (Capsicum frutescens L.) is a commodity that has the opportunity to be commercially cultivated. Giving manure to plants is one of the efforts to increase crop production. One alternative manure that can be used is Quail Manure. How to application of fertilizers that can be done by Broadcasting, Ring plancement, Spot plancement. The purpose of this study was to determine the effect of dose and how to provide Quail Manure on the growth and yield of cayenne pepper. The research used a Randomized Block Design (RBD) 2 factors. Factor I (doses of Quail Manure (P)) are p1 = 10 t ha-1; p2 = 15 t ha-1; p3 = 20 t ha-1 and Factor II (method of applying Quail Manure (H)) are h1 = Broadcasting, h2 = Ring Plancement, h3 = Spot Plancement. Both factors were combined to obtain 27 experiments with 9 combinations and 3 repetations. The results showed that the interaction of quantities and ways of giving Quail Manure to the growth and yield of cayenne pepper had a significant effect of dose of Quail Manure fertilizer 10 t ha-1+broadcasting with the total production of 201.62 pieces cayenne pepper and single factor in the way of giving quail manure by broadcasting shows a very real effect on the weight of 100 seeds that is 91.70 g.